Cytotoxicity of sesquiterpene alkaloids from Nuphar plants toward sensitive and drug-resistant cell lines. Issue 12 (8th November 2018) - Fukaya, Masashi; Nakamura, Seikou; Hegazy, Mohamed Elamir F.; Sugimoto, Yoshikazu; Hayashi, Noriko; Nakashima, Souichi; Yoshikawa, Masayuki; Efferth, Thomas; Matsuda, Hisashi
Abstract : Thioalkaloids isolated from Nuphar plants showed cytotoxic effects on sensitive and resistant cancer cell lines. Abstract : Multi-drug resistance (MDR) is a critical problem in cancer chemotherapy. MDR causes the overexpression of ATP-binding cassette (ABC) transporters and mutations in tumor suppressor genes and oncogenes. To tackle this issue, in this study, we focused on Nuphar plants, which have been traditionally used as food. Sesquiterpene alkaloids (1–3 ) were isolated from N. japonicum and dimeric sesquiterpene thioalkaloids (4–10 ) were isolated from N. pumilum. P-glycoprotein-overexpressing CEM/ADR5000 cells were cross-resistant to 6, 6′-dihydroxythiobinupharidine (10 ). Using in silico molecular docking, we calculated the binding energies and simulated the interactions of these compounds with the corresponding amino acid residues at the binding site of P-gp. In addition, we investigated the cytotoxicity of these compounds towards cell lines overexpressing other ABC transporters (BCRP, ABCB5), cell lines with a knocked out tumor suppressor gene TP53 or cell lines overexpressing a deletion-activated EGFR oncogene. These cell lines were sensitive or only minimally cross-resistant to these compounds compared with their corresponding wild-type cell lines.